Urejanje mobilnih življenj: Marginalizirani Maročani v transnacionalnem prostoru - Juntunen, Marko (Two Homelands, 2013)
The article traces, by means of extended ethnographic participant observation, the cultural construction of a particular type of male marginal mobility, namely that of economically marginalised Moroccan migrant men. For these men, the departure from Morocco as irregular migrants to Europe appeared as a means to escape a life without a horizon. They faced lethal dangers during their journeys across the Strait of Gibraltar in small open boats, and Spain appeared unwelcoming to them, since the traditional sector of migrant labour, industrial work, could no longer absorb them. These men had very few other options than to invest in transnationalising the distinctive ethos of dabbar, i.e. ‘arranging’ survival strategies and social relations in the unregulated and lowest echelons of the labour market in Spain. For a large number of these Moroccans, permanent EU residence and citizenship turned into means of broadening the sphere of dabbar. Many of these men currently engage in transnational trading activities of second-hand goods, including small electronic devices, shoes and clothes and household utensils.